The Introduction of Macroprudential Measures for the Irish Mortgage Market - Cassidy, Mark; Hallissey, Niamh (The Economic and Social Review, 2016)
In February 2015 the Central Bank of Ireland introduced macroprudential measures for the Irish mortgage market in the form of limits on new lending at high loan-to-value and loan-toincome ratios. The objectives of the measures are to enhance resilience of banks and households to financial shocks and to curb cyclical tendencies in the mortgage market. The timing of the introduction of the measures was carefully considered and reflected emerging imbalances in the market as well as existing vulnerabilities in the household and banking sectors. While similar measures have been introduced in other jurisdictions, the design and application of the measures differ across countries. Some specific aspects of the design of the Irish measures include differentiated treatment for first-time buyers, buy-to-let borrowers and homeowners in negative equity. This paper discusses the rationale for the introduction of the measures as well as issues relating to their design and implementation.